A 25 MHz crystal less clock generator with background calibration against process and temperature variation. (May 2016) - Yang, Wei-Bin; Hong, Ming-Hao
Abstract: This paper presents a crystal-less clock generator using an automatic process and temperature variation calibration technique. The crystal-less clock generator comprises a voltage-controlled oscillator (VCO), differential-input-single-output (DISO) circuit, and frequency-to-voltage converter (FVC). The VCO was developed using a four-stage differential ring oscillator to generate an output frequency of 25 MHz. The DISO circuit ensures a full-swing output voltage swing of the clock generator and a 50% duty cycle. The output clock is integrated by the FVC circuit to generate an analog voltage signal to control the VCO's oscillation frequencies. The FVC can compensate and calibrate the VCO to provide a stable output frequency through the closed-loop system. The chip was fabricated using a 0.18 µm standard CMOS process with a 0.9 V supply voltage. The measured temperature coefficient was 513 ppm/°C in the temperature range of −40°C to 125°C at a 25-MHz output frequency.